Children can help with the climate change - ΜΠΕΚΑ ΑΠΟΣΤΟΛΙΑ ΒΑΣΙΛΕΙΟΥ (Open Schools Journal for Open Science, 2021)
Climate change issues are a big concern for all people now days. Climate is the average of the weather (temperature, rainfall, humidity, etc) prevailing in one place (Shepherd, Shindell, O’Carroll, 2005). Climate change is due to natural or anthropogenic causes. The project aimed at raising interest on climate issues, risks and impacts for students, so as their activities could contribute positively to the reduction of climate change and be aware of the fact that natural resources are being exhausted and therefore only by adopting an Eco-sustainable lifestyle could limit the damage. Students organized different activities such as brain storming, crafts, experiments, robotic and they also tried to raise parents and society awareness of climate change phenomena and the related impacts with events such as inviting experts and publishing results on websites and local press. The aims of the project were: strengthen children’s knowledge of climate change and understand the relationship of drought and water scarcity to climate change.